Post-Truth politics: Euroscepticism in the political discourse of the Italian and British press - O. A. Ksenzenko (Vestnik MGIMO-Universiteta)
Book review: Paul Rowinski. 2021. Post-Truth, Post-Press, Post-Europe. Euroscepticism and the Crisis of Political Communication. Palgrave Macmillan Cham. 2021. 252 p. https://doi. org/10.1007/978-3-030-55571-9.